Business Incubation Strategy of Information Technology in Stimulating Innovation and Supporting SME Growth in the Community Environment - Sutrisno, Sutrisno; Hadi, Dwi Prastiyo; Prayitno; Wibowo, Bagus Yunianto (Technology and Society Perspectives (TACIT), 2024)
The growth of Micro, Small, and Medium Enterprises (MSMEs) has become a key driver of the economy in many countries, including Indonesia. MSMEs not only make significant contributions to job creation but also play a crucial role in supporting economic inclusion and reducing socio-economic disparities. This research aims to provide an in-depth understanding of the business incubation strategy of information technology and its impact on the growth of MSMEs in the community environment. This study utilizes a literature review method to compile a comprehensive understanding of the topic and gather data from Google Scholar for the years 1994-2023. The results of the study indicate that the business incubation strategy of information technology has significant potential in stimulating innovation and supporting the growth of Micro, Small, and Medium Enterprises (MSMEs) in the community environment. By providing access, training, collaboration, and appropriate financial support, MSMEs can more effectively utilize information technology to enhance their competitiveness and productivity.